The Quality of Colostrum and Its Effects on Calves Growth Characteristics in Holstein Cattle - K&ouml -; Ali Kaygısız; Mustafa Köse (Journal of Agricultural Sciences)
This study was carried out to determine colostrum quality in Holstein Cows. Colostrum quality has been estimated by using a colostrometer. The colostrometer works by measuring the specific gravity of colostrum and then takein advantage of the linear relationship between the specific gravity of colostrum and its Ig concentration. Among the 59 colostrum samples tested, 15 25% samples were found to be good, 32 samples 55 % were intermediate and the other12 samples 20% were low concentration. The effect of age of dam and dry period on colostrum quality were found to be significant P0.05 . The effect of age of dam and colostrum quality on calf birth weight were found to be significant P